مساهمة التدقيق الداخلي في تقييم فعالية نظام الرقابة الداخلية بالاعتماد على أسلوب خرائط التدفق – دراسة حالة مؤسسة ميناء الجزائر– - بوقدوم مريم; عثماني مصطفى (جامعة الوادي University of Eloued, 2024)
تهدف هذه الدراسة إلى معرفة كيفية مساهمة التدقيق الداخلي في تقييم نظام الرقابة الداخلية، وذلك من خلال القيام بدراسة تطبيقية في مؤسسة ميناء الجزائر، تتمثل في تقييم نظام الرقابة الداخلي الفرعي لوظيفة الشراء، بالاعتماد على أحد أساليب تقييم نظام الرقابة الداخلية والمتمثل في "خرائط التدفق"، خلال الفترة الممتدة 2018/2020. حيث توصلت هذه الدراسة إلا أن نظام الرقابة الداخلية لمؤسسة ميناء الجزائر يحتوي على مجموعة من نقاط القوة تزيد من فعاليته، كما تم اكتشاف عدة نقاط ضعف ينبغي الحد منها، حيث تم التوصل الى أن التدقيق الداخلي يعتبر كآلية رقابية وظيفتها التأكد من تنفيد ضوابط وإجراءات نظام الرقابة الداخلية مايساهم في تحسين فعالية هذا الأخير، والذي بدوره يعتبر كدعامة لوظيفة التدقيق الداخلي. This study aims to find out how internal audit contributes to evaluating the internal control system, by conducting an applied study in the Algiers Port Corporation, which consists of evaluating the internal control subsystem for the purchasing function, relying on one of the methods of evaluating the internal control system, which is “flow maps.”, during the period extending 2018/2020. This study concluded that the internal control system of the Algiers Port Corporation contains a set of strengths that increase its effectiveness, and several weak points were discovered that should be reducedInternal audit was found to be a supervisory mechanism whose function is to ensure the implementation of the controls and procedures of the internal control system, which contributes to improving the latter's effectiveness, which in turn is considered as a pillar of the internal audit function
The contribution of internal audit in evaluating the effectiveness of the internal control system based on the flow mapsmethod -a case study of the Algiers Port Corporation -
Keywords: نظام الرقابة الداخلية; تدقيق داخلي; رقابة داخلية; خرائط التدفق; Internal control system; Internal audit; internal control; Flow maps